The 'Continental' Tradition?. (30th June 2014) - Montefiore, Alan
Abstract There is – of course – no one such thing as the continental tradition in philosophy, but rather a whole discordant family of notably distinct traditions. They are, nevertheless, broadly recognisable to each other. For much of the last century, however, most of those engaged in or with philosophy in continental Europe, on the one hand, and in the English-speaking world, on the other hand, had surprisingly little knowledge of, interest in or even respect for what was going on in the other. Happily, the situation today is vastly improved on each side of the philosophical channel. What follows is an attempt to gain some understanding of the background to this long-standing (and still to some diminishing extent persistent) mutual incomprehension from the standpoint of one who came to philosophy as a PPE student in the Oxford of the late 1940s.